ESENSI PENCIPTAAN ALAM SEMESTA DALAM KONSEP RUANG DAN WAKTU PERSPEKTIF FILSAFAT MUHAMMAD IQBAL - Sulhatul Habibah; Hurin Innihayatus Sa’adah (LPPM UNISDA, 2022)
ABSTRACT Space and time are cosmological issues that present a long dialogue between philosophers and scientists. Whether space and time are objective or subjective, dynamic or fixed. The method used in writing this article is descriptive qualitative with a literature approach. The results of the analysis of the concept of space and time in Muhammad Iqbal's philosophy to understand the essence of the creation of the universe, namely Iqbal based the process of creating the universe on the Qur'an, the continuation of time in 6 periods / day. Space as a container of things, and for Iqbal the quality of travel in time is the most significant aspect of experience, receives special emphasis in the Qur'an, which provides the best clues about the true nature of reality. The essence of time for Iqbal is spiritual. The basic nature of reality is spiritual, the time spent is filled with spiritual strengthening, by subduing the human ego, the God entity within him will unite. God's space and time by the Qur'an is called the unul kitab with a universe that is free from the network of causes and effects compiled from one super-eternal present.